Probabilistic reliability framework for assessment of concrete fatigue of existing RC bridge deck slabs using data from monitoring. (15th December 2019) - Mankar, Amol; Bayane, Imane; Sørensen, John Dalsgaard; Brühwiler, Eugen
Highlights: The current study proposes a framework for probabilistic reliability assessment of existing reinforced concrete structures. A new stochastic SN model for compression-fatigue of concrete. Results show two factors play a very important role in the reliability level for fatigue of concrete structures. a. The accuracy in estimating the fatigue action effects. b. The uncertainty related to the static compressive strength of concrete. Abstract: Assessment of existing bridge structures for inherent safety level or for lifetime extension purposes is often more challenging than designing new ones. With increasing magnitude and frequency of axle loads, reinforced concrete bridge decks are susceptible to fatigue failure for which they have not been initially designed. Fatigue verification and prediction of remaining service duration may turn out to be critical for civil infrastructure satisfying the required reliability. These structures are exposed to stochastic loading (e.g. vehicle loads, temperature loads); on the resistance side, reinforced concrete also behaves in a stochastic way. This paper presents a probabilistic reliability framework for assessment of future service duration, which includes probabilistic modelling of actions based on large monitoring data and probabilistic modelling of fatigue resistance based on test data. A case study for the steel - reinforced concrete slab of the Crêt de l'Anneau Viaduct is presented along with calibration of resistance partial safety factors for lifetime extension.